2010
DOI: 10.1038/hr.2010.184
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RGS2 deficiency on the therapeutic effect of telmisartan in angiotensin II-induced aortic aneurysm

Abstract: Regulator of G-protein signaling 2 (RGS2) negatively regulates the signaling of G-protein-coupled receptors, such as the angiotensin II (AngII) type 1 receptor by accelerating the inactivation of Gaq. Rgs2-deficient mice show increased sensitivity and prolonged responsiveness to vasoconstrictors, and genetic variations in the RGS2 gene are associated with hypertension in humans. This study aimed to clarify whether Rgs2 deficiency contributes to the development of vascular remodeling and therapeutic efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Both RGS2 þ/À and RGS2 À/À mice are very hypertensive with increased systemic and renal vascular resistance and hypertrophy of the renal arterial vasculature (Fujio, 2010;Gurley et al, 2010;Heximer et al, 2003;Matsumoto et al, 2010;Momen et al, 2014;Ota et al, 2013;Sjogren et al, 2012;Sugimoto et al, 2010;Tsang et al, 2010). These RGS2 absent mice have excessive and prolonged Ca þþ signaling to vasconstrictors such as ATP acting on P2Y receptors.…”
Section: Rgs2mentioning
confidence: 96%
“…Both RGS2 þ/À and RGS2 À/À mice are very hypertensive with increased systemic and renal vascular resistance and hypertrophy of the renal arterial vasculature (Fujio, 2010;Gurley et al, 2010;Heximer et al, 2003;Matsumoto et al, 2010;Momen et al, 2014;Ota et al, 2013;Sjogren et al, 2012;Sugimoto et al, 2010;Tsang et al, 2010). These RGS2 absent mice have excessive and prolonged Ca þþ signaling to vasconstrictors such as ATP acting on P2Y receptors.…”
Section: Rgs2mentioning
confidence: 96%
“…One study found that RGS2 mRNA levels increased because of the RGS2 (-391 C>G) mutation [ 15 ]. The antihypertensive and organ protection effects of telmisartan or candesartan are greater in RGS2 -/- mice than in RGS2 +/+ mice [ 24 , 25 ]. Previous data support our results that the RGS2 (-391 C>G) genetic variation was associated with responses to ACE inhibitors and ARB but not with CCB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, telmisartan significantly improved the survival rates and suppressed vascular remodeling in an RGS2 -deficient mice model. Other studies suggest that Ang II causes a rapid and transient increase in RGS2 mRNA levels, which can be blocked by the calcium channel blocker (CCB) nifedipine[ 6 , 13 ]. Notably, one recent study observed that a cAMP-response element played a critical role in activating the RGS2 promoter, and the -867 to -367 bp region had an integral role in basal promoter activation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II is also involved in the formation of aneurysms [40], and telmisartan has been found to prevent their formation in two animal models. In mice deficient in regulator of G-protein signaling 2 (RGS2; a negative regulator of AT 1 receptors), telmisartan reduced the incidence of aneurysms [41]. In rat aortic tissue, telmisartan prevented abdominal aortic aneurysm progression independently of reducing BP, by inhibition of proteolysis, apoptosis, and inflammation [42].…”
Section: Arterial Stiffness and Vascular Changesmentioning
confidence: 99%